Pengaruh Pendidikan, Kesehatan, Teknologi, Upah Terhadap Tingkat Partisipasi Angkatan Kerja - Hanifah Khoirunnisa; Nairobi Nairobi; Arif Darmawan (CV. ITTC INDONESIA, 2025)
This research investigates the effects of education, health, technology, and wage factors on the Labor Force Participation Rate (LFPR) across provinces in Sumatra Island from 2014 to 2024. The explanatory variables include Expected Years of Schooling (EYS), Life Expectancy (LE), the Information and Communication Technology Development Index (ICTDI), and the Provincial Minimum Wage (PMW). Secondary data sourced from the Central Bureau of Statistics were analyzed using panel data regression, employing the Fixed Effect Model (FEM) via Eviews 12 software.The empirical results indicate that EYS has a positive yet statistically insignificant relationship with LFPR. LE exerts a positive and significant influence, suggesting that improved public health fosters greater participation in the labor market. ICTDI demonstrates a negative and significant effect, implying that technological advancement may substitute labor in certain sectors. PMW shows a positive but insignificant association with LFPR. Collectively, the four variables significantly explain variations in LFPR, with an R-squared value of 82.73%. These findings highlight the importance of enhancing public health, ensuring equitable access to technology, and implementing well-targeted education and wage policies to strengthen labor force participation in Sumatra.